The Effect of “Si Andi” Flashcard Games on Improving Personal Safety Skills - Maritza, Erra Khanza; Scarvanovi, Berliana Widi (Program Studi Magister Pendidikan Anak Usia Dini, 2024)
One of the highest and continually increasing phenomena of violence in Indonesia is sexual abuse. The most frequent victims of this phenomenon are early childhood. The purpose of this study is to determine the influence of the